The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1542/peds.2012-1427m
|View full text |Cite
|
Sign up to set email alerts
|

Management of Bronchiolitis in the Emergency Department: Impact of Evidence-Based Guidelines?

Abstract: OBJECTIVE: Recent practice guidelines from the American Academy of Pediatrics recommend limiting use of bronchodilators, corticosteroids, antibiotics, and diagnostic testing for patients with bronchiolitis. We sought to determine the association of the evidence-based guidelines with bronchiolitis care in the emergency department (ED). METHODS:We analyzed data from the National Hospital Ambulatory Medical Care Survey, a nationally representative sample of ED visits. We compared utilization for patient visits be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 36 publications
5
85
1
3
Order By: Relevance
“…17 By using the National Hospital Ambulatory Medical Care Survey (NHAMCS), a nationally representative sample of ED visits, the authors found a decrease in diagnostic imaging with CXR but no decrease in nonrecommended therapies, such as bronchodilators, corticosteroids, and antibiotics. In contrast, our study showed a reduction of diagnostic tests, both CXR and CBC count, and nonrecommended medications.…”
Section: Discussionmentioning
confidence: 99%
“…17 By using the National Hospital Ambulatory Medical Care Survey (NHAMCS), a nationally representative sample of ED visits, the authors found a decrease in diagnostic imaging with CXR but no decrease in nonrecommended therapies, such as bronchodilators, corticosteroids, and antibiotics. In contrast, our study showed a reduction of diagnostic tests, both CXR and CBC count, and nonrecommended medications.…”
Section: Discussionmentioning
confidence: 99%
“…Admission rates have between reported at 13% among a cohort of patients treated at either a pediatric or a general hospital, 39 at 31% among a cohort treated at pediatric emergency departments, 9 and at 37% among a cohort treated at a general hospital. 26 The variation may reflect differences in illness severity as well as differences in physician comfort in managing bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent national study of ED visits also revealed that after the publication of the 2006 AAP bronchiolitis guideline, CXR rates decreased by one-quarter nationally, whereas there was no change in the use of antibiotics and bronchodilators. 24 The choice to use albuterol was also likely indicative of the strength of the evidence and resulting recommendation. In the guideline, the recommendation is qualified with a "may" as in "trial dose of albuterol may be considered" in contrast to one that says "CXR not routinely recommended.…”
Section: Discussionmentioning
confidence: 99%